Bimbingan Kelompok dengan Teknik Role Playing untuk Menanamkan Solidaritas pada Peserta Didik - Juhaena, Jihan Sephiani; Putri, Ervita Adelia; Rahman, Faridh Ajrur (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2022)
This research aims to describe and analyse the effectiveness of the role of guidance role playing technique (play the role of) to infuse solidarity on students by using the methodology of the literature review as a comparison and reference material by looking at thejournal derived from google scholar, a thesis of google scholar and a book derived from google book. Engineering group guidance role playing is the right choice to strengthen relationships, social students can think that attitude should be changed or defended. Owned because without the help of others, students will suffer evaluate attitude as well as the value of owned. Has been discussed at the studies jurnal passed away that the services guidance by a group of role playing can influence in imparting or increase solidarity with us on students. The research results show that counseling teacher needs to give guidance services groups with role playing technique so that they can play primary school students, mimicked, discern between role of that need to be adopted or do not have to adopted, actively participate to the discussion, become thedestination of the behavior and capable of developing better solidarity among students is expected to moving forward.